Synthesis and biological evaluation of certain 3-substituted benzylideneamino-2-(4-nitrophenyl)quinazolin-4(3H)-one derivatives. (17th June 2014) - Alafeefy, Ahmed M.; Awaad, Amani S.; Abdel-Aziz, Hatem A.; El-Meligy, Reham M.; Zain, Mohamed E.; Al-Outhman, Mounerah R.; Bacha, Abir B.
Abstract: Certain new 3 H -quinazolin-4-one Schiff's bases were synthesized and screened for their activities against ulcerative colitis "UC". Their activity against phospholipase A2 and protease enzymes was also investigated. Some compounds possessed remarkable effect with different potentials against acetic acid-induced colitis model in rats. Compound14 (50 mg/kg) was more effective than dexamesathone (0.01 mg/kg). It produced 79.78% protection of control colitis; however, compound13 produced 75.80% protection and was considered as effective as dexamesathone with 75.30% protection. The observed results could be explained partially by their anti-inflammatory activities which appear as phospholipase A2 ( h GIIA) and/or through protease inhibitor potentials. However, all the compounds under test showed preferential inhibition towards h G-IIA type of PLA2 rather than DrG-IB with varying degrees. Interestingly, compounds14, 13, 12 and11 displayed excellent inhibitory activity against phospholipase A2 accompanied by protease inhibitory profile.